Research on internal gravity waves in the Martian atmosphere based on Tianwen-1 and Mars Global Surveyor occultation data - Luo Xiao; CunYing Xiao; Xiong Hu; ZeWei Wang; XiaoQi Wu (Earth and Planetary Physics)
Internal gravity waves (IGWs) are critical in driving Martian atmospheric motion and phenomena. This study investigates Martian IGWs by using high-resolution data from China’s Tianwen-1 mission and the National Aeronautics and Space Administration’s Mars Global Surveyor (MGS) by the radio occultation (RO) technique. Key IGW parameters, such as vertical and horizontal wavelengths, intrinsic frequency, and energy density, are extracted based on vertical temperature profiles from the Martian surface to ~50 km altitude. Data reveal that the Martian IGWs are predominantly small-scale waves, with vertical wavelengths between 6 and 13 km and horizontal wavelengths extending to thousands of kilometers. These waves propagate almost vertically and exhibit low intrinsic frequencies close to the inertial frequency, with the characteristic of low-frequency inertial IGWs. Tianwen-1 data indicate stronger IGW activity, higher energy density, and less dissipation than MGS data in the northern hemisphere. Moreover, MGS data in the southern hemisphere show higher buoyancy frequencies and lower vertical wavelengths, suggesting more stable atmospheric conditions conducive to IGW propagation. These extracted IGW characteristics can enhance our understanding of the atmospheric dynamics on Mars and contribute valuable information for parameterization in global circulation models.